KONFLIK PSIKOLOGIS SARA CREWE DALAM NOVEL A LITTLE PRINCESS KARYA FRANCES HODGSON BURNETT - Maharani, Bernadita Ruri (LANTERN (Journal on English Language, Culture and Literature), 2013)
A novel is usually a reflection for the life of society at the time the novel was published. Through the study of personality based on the main character of a novel, the specific information of a character’s nature and behavior in a storyline could be extracted further. Personality research which is based on the main character of a novel regularly tends to appear with psychological affect. This research was conducted to fulfill two purposes. The first particular purpose of this research was to describe and express the main character's personality in the A Little Princess a work by Frances Hodgson Burnett, and the second purpose was to describe and define the function of the relationship between the other figures on the development of the main character lives in the novel The Little Princess. The methods used in this research are the library study and descriptive approach method. The data is observational data study. Observational data or object of research is a form of a novel written by Frances Hodgson Burnett then examined one by one section in the notes field. In addition to these sources, the data was also obtained from the method of approach of the personality theory developed by Sigmund Freud which is applied into the main character of A Little Princess. Keywords: novel, psychological conflict, psychoanalytic theory